PENGARUH PENERAPAN GREEN ACCOUNTINGTERHADAP TINGKAT PROFITABILITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aliah Pratiwi; Nafisah Nurulrahmatiah; Intisari Haryanti; Nurul Huda; Ita Iftitah (Jurnal Ilmiah Satyagraha, 2023)
This study aims to determine the effect of the application of Green Accounting onthe level of profitability of pharmaceutical companies listed on the BEI. Greenaccounting emerged as a solution to solve the deadlock of problems that occurbetween economic actors who carry out activities that have an environmentalimpact and people who feel the impact of environmental activities. This researchwas conducted on pharmaceutical companies listed on the Indonesia StockExchange using the 2017-2021 annual report. The sample in this study were 9pharmaceutical companies listed on the IDX. The data used is secondary dataobtained from www.idx.co.id. The data analysis method used in this study is thepanel regression model. Data processing uses the Smart-PLS version 3.0application. From this study, it was found that the Environmental DevelopmentIndex (IBL) or environmental costs had no effect on profitability. Likewise,Environmental Performance (PROPER) also has no effect on profitability.